Chest Wall Resection for Recurrent Breast Cancer in the Modern Era: A Systematic Review and Meta-analysis. Issue 4 (April 2018) - Wakeam, Elliot; Acuna, Sergio A.; Keshavjee, Shaf
Abstract : Objective: To review the literature on chest wall resection for recurrent breast cancer and evaluate overall survival (OS) and quality-of-life (QOL) outcomes. Background: Full-thickness chest wall resection for recurrent breast cancer is controversial, as historically these recurrences have been thought of as a harbinger of systemic disease. Methods: A systematic search in MEDLINE, EMBASE, and Cochrane CENTRAL identified 48 eligible studies, all retrospective, accounting for 1305 patients. The review is reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Primary end points were patient-centered QOL outcomes and OS; secondary outcomes included disease-free survival (DFS) and 30-day morbidity. Risk of bias was assessed using the Methodological Index for Non-Randomized Studies instrument and the Oxford Centre for Evidence-Based Medicine's levels of evidence tool. Random-effects meta-analysis was used to create pooled estimates. Meta-regressions and sensitivity analyses were used to explore study heterogeneity by age, year of publication, risk of bias, and surgical intent (curative vs palliative). Results: Studies consistently reported excellent OS and DFS in properly selected patients. Pooled estimates for 5-year OS in all studies and those from the past 15 years were 40.8% [95% confidence interval (CI) 35.2–46.7) and 43.1% (95% CI 35.8–50.7), whereas pooled 5-year DFS was 27.1% (95% CI 16.6–41.0). Eight studies reported excellent outcomes related to QOL. Mortality was consistently low (<1%) and 30-day pooled morbidity was 20.2% (95% CI 15.3%–26.3%). Study quality varied, and risk of selection bias in included studies was high. Conclusions: Full-thickness chest wall resection can be performed with excellent survival and low morbidity. Few studies report on QOL; prospective studies should focus on patient-centered outcomes in this population. Abstract : Supplemental Digital Content is available in the text